Development of safety performance model based on safety climate and safety competence in paramedic training institute in Malaysia / Intan Suraya Noor Arzahan - Noor Arzahan, Intan Suraya (2022)
Meeting the objectives of Occupational Safety and Health Master Plan (OSHMP2020) such as immediate reduction of accident rate and inculcating a preventive safety culture, the issue of safety performance at the government paramedic training institute in Malaysia was identified. The issues include what factors can influence the improvement of safety performance and contribute to a preventive safety culture in the institute. It became a question when looking at the increasing trend of incidents reported to the Department of Occupational Safety and Health (DOSH) Malaysia by the government sector and local authorities that recorded an increase in incident rates from year to year. This research aims to evaluate the safety climate and safety competence indicators and their influence on safety performance in achieving the main objective of developing a safety performance model based on safety climate and safety competence in paramedic training institute in Malaysia. This research used a stratified random sampling strategy to obtain data from 258 respondents who completed a self-administered questionnaire based on five dimensions of predicted safety performance factors.